CAPTURING TUBERCULAR MENINGITIS PROGRESSION IN CHILDREN WITH MULTI-SLICED COMPUTED TOMOGRAPHY (MSCT) SCAN: A PROSPECTIVE CASE REPORT - Sherlyta Revania Ranuh (Berkala Ilmiah Kedokteran Duta Wacana, 2020)
Background: Tubercular meningitis in children poses a diagnostic challenge, either for its detection and follow-up. Neuroimaging is essential in the diagnosis process and early identification of complication or sequelae. Computed tomography (CT) scan is widely available in secondary and tertiary hospitals in Indonesia, which would improve the management of paediatric tubercular meningitis case. Objective: To describe the clinical progression of a child with tubercular meningitis from detection to sequelae at Bethesda Hospital, Yogyakarta. Case description: A 7-year-old boy was admitted to the emergency unit with acute headache, vomiting, and prolonged fever. Tuberculosis transmission indicated from the mother, which on TB treatment. Non-contrast multi-sliced computed tomography (MSCT) scan was performed on the first-day admission, on the 8th day of admission, before and after VP-shunt procedure for life-threatening hydrocephalus and the follow-up. There was an obvious disease progression shown by CT scan from the early stage, the onset of hydrocephalus, deteriorating hydrocephalus, and post-VP-shunt procedure. The periventricular infarct extended over time, concordant with worsening symptoms. Conclusion: Paediatric tubercular meningitis diagnosis relies on accurate neuroimaging studies to identify the specific sign. In the disease progression, the sign as early as slight hyperdensity should lead to meningitis diagnosis, and earlier treatment of hydrocephalus might prevent further debilitating sequelae or even fatal complications of tubercular meningitis.